Impact of co‐infection with Lepeophtheirus salmonis and Moritella viscosa on inflammatory and immune responses of Atlantic salmon (Salmo salar). Issue 4 (25th February 2020) - Carvalho, Laura A.; Whyte, Shona K.; Braden, Laura M.; Purcell, Sara L.; Manning, Anthony J.; Muckle, Anne; Fast, Mark D.
Abstract: This study was conducted to determine the effects of a co‐infection with Moritella viscosa at different exposure levels of sea lice Lepeophtheirus salmonis in Atlantic salmon ( Salmo salar ). M. viscosa (1.14 × 10 6  cfu/ml) was introduced to all experimental tanks at 10 days post‐lice infection (dpLs). Mean lice counts decreased over time in both the medium lice co‐infection (31.5 ± 19.0 at 7 dpLs; 16.9 ± 9.3 at 46 dpLs) and high lice co‐infection (62.0 ± 10.8 at 7 dpLs; 37.6 ± 11.3 at 46 dpLs). There were significantly higher mortalities and more severe skin lesions in the high lice co‐infected group compared to medium lice co‐infected group or M. viscosa ‐only infection. Quantitative gene expression analysis detected a significant upregulation of genes in skin from the high lice co‐infection group consistent with severe inflammation ( il‐8, mmp‐9, hep, saa ). Skin lesions retrieved throughout the study were positive for M. viscosa growth, but these were rarely located in regions associated with lice. These results suggest that while M. viscosa infection itself may induce skin lesion development in salmon, co‐infection with high numbers of lice can enhance this impact and significantly reduce the ability of these lesions to resolve, resulting in increased mortality.